<span> 5 – 2(x – 4) = 3(5 – x) – 4x
5-2х+8=15-3х-4х
13-2х=15-7х
-2х+7х=15-13
5х=2
х=2/5
х=0.4</span>
1
сtg3x-ctgx=0
sin(3x-x)/sin3x*sinx=0
sin2x=0 U sin3x*sinx≠0
2x=πn⇒x=πn/2,n∈z U x≠πk,k∈z U x≠πm/3,m∈z
x=πn/2,n∈z U n≠2m/3,m∈z
3
sin(2x+4x)/cos2xcos4x=sin(5x+x)/cos5xcosx
sin6x/cos2xcos4x-sin6x/cos5xcosx=0
sin6x(cos5xcosx-cos2xcos4x)/cosxcos2xcos4xcos5x=0
cosxcos2xcos4xcos5x≠0
sin6x=0⇒x=πn/6,n∈z
cos5xcosx-cos2xcos4x=0
1/2*cos4x+1/2*cos6x-1/2*cos2x-1/2*cos6x=0
1/2*cos4x-1/2*cos2x=0
-1/2*2sinxsin3x=0
sinx=0⇒x=πk,k∈z
sin3x=0⇒x=πm/3,m∈z
4х-12=х+15
4х-х=12+15
3х=27
х=9
3*(3,4-х)=9
3,4-х= 9:3
3,4х=3
3,4-3=0,4